CORRELATION BETWEEN METABOLIC CONTROL AND OXIDATIVE STRESS IN TYPE 1 DIABETES: MALONDIALDEHYDE AS A PROTECTIVE FACTOR - Anca Daniela Pînzaru; Cristina Maria Mihai; Tatiana Chisnoiu; Alexandru Cosmin Pantazi; Elena Grosan; Simona Claudia Cambrea; Ileana Ion (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study. This study aimed to evaluate malondialdehyde status and dyslipidemia in diabetic children. In children, type 1 diabetes mellitus (T1DM) is considered one of the most common chronic autoimmune diseases. The first step is detecting insulin deficiency expressed by hyperglycemia. The short- and long-term effects are significant and affect all body parts: blood vessels, eyes, kidneys, brain, heart, and nerves. Persistent hyperglycemia generates reactive oxygen species (ROS) / free radicals through metabolic abnormalities such as glucose autooxidation and non-enzymatic glycation. Materials and methods. This study included 50 children with T1DM with a mean age of 7.6 years. Important elements were evaluated to establish clear indicators of atherosclerotic activity (lipoperoxidation, protein oxidation, changes in the status of antioxidant defense systems, plasma oxygen radical absorbance capacity (ORAC), glycated hemoglobin (HbA1c), total cholesterol, and triglycerides). Results. Malondialdehyde (MDA) and lipid levels were correlated and significantly higher (0,87 ± 0.2 versus 1,8 ± 0,87 µmol/L, 66,33 +/-14,21 versus 43,33 +/- 7,2 respectively; P < 0.001), and a significant reduction in plasma total antioxidant capacity. Conclusions. MDA levels presented elevated values, indicating the negative connection between atherosclerotic risk factors and MDA. This important conclusion can be drawn every time a patient with type 1 diabetes presents LDL excess levels, therefore representing an increased lipid peroxidation resulting in higher MDA levels. From this point, the correlation between hyperglycemia (the main source of increased oxidative stress) in patients with poor metabolic control and MDA is not the only path to anticipate the risk of atherosclerotic complications.